Reform in the balance : the defense of literary culture in mid-Tang China - DeBlasi, Anthony (SUNY series in Chinese philosophy and culture., 2002)
Anthony DeBlasi offers a remapping of China's intellectual landscape during the late-eighth and early-ninth centuries. Recreating a world of intense philosophical debate, influenced by political uncertainty and social disorder, he reveals the logic behind the period's most popular philosophical positions. Reform in the Balance casts aside traditional evaluations of the predominance of the Ancient Style Movement (guwen) during this era. Building on recent scholarship and his own reading of Tang sources, the author argues that the period's dominant intellectual position advocated moderately conservative cultural reform designed to defend literary pursuits and the broader cultural tradition from more strident critics.